The Role of Caspase-2 in Regulating Cell Fate - Vigneswara, Vasanthy (Cells, 2020)
Caspase-2 is the most evolutionarily conserved member of the mammalian caspase family and has been implicated in both apoptotic and non-apoptotic signaling pathways, including tumor suppression, cell cycle regulation, and DNA repair. A myriad of signaling molecules is associated with the tight regulation of caspase-2 to mediate multiple cellular processes far beyond apoptotic cell death. This review provides a comprehensive overview of the literature pertaining to possible sophisticated molecular mechanisms underlying the multifaceted process of caspase-2 activation and to highlight its interplay between factors that promote or suppress apoptosis in a complicated regulatory network that determines the fate of a cell from its birth and throughout its life.